Transient Kupffer cell depletion and subsequent replacement by infiltrating monocyte‐derived cells does not alter the induction or progression of hepatocellular carcinoma. Issue 12 (20th March 2023) - Vanderborght, Bart; De Muynck, Kevin; Gijbels, Eva; Lefere, Sander; Scott, Charlotte L.; Guilliams, Martin; Beschin, Alain; Vinken, Mathieu; Verhelst, Xavier; Geerts, Anja; Van Vlierberghe, Hans; Devisscher, Lindsey
Abstract: Due to a combination of rapid disease progression and the lack of curative treatment options, hepatocellular carcinoma (HCC) is one of the deadliest cancers worldwide. Infiltrated, monocyte‐derived, tumor‐associated macrophages are known to play a role in HCC pathogenesis, but the involvement of Kupffer cells (KCs) remains elusive. Here, we used the Clec4F‐diphteria toxin receptor transgenic mouse model to specifically investigate the effect of KC depletion on HCC initiation, progression and neoplastic growth following liver resection. For this purpose, several HCC mouse models with varying underlying etiologies were used and partial hepatectomy was performed. Our results show that in HCC, developed on a fibrotic or non‐alcoholic steatohepatitis background, depletion of embryonic KCs at the onset of HCC induction and the subsequent replacement by monocyte‐derived KCs does not affect the tumor burden, tumor microenvironment or the phenotype of isolated KCs at end‐stage disease. In non‐chronic liver disease‐associated diethylnitrosamine‐induced HCC, ablation of Clec4F + KCs did not alter tumor progression or neoplastic growth following liver resection. Our results show that temporal ablation of resident KCs does not impact HCC pathogenesis, neither in the induction phase nor in advanced disease, and indicate that bone marrow‐derived KCs are able to swiftly repopulate the available KC niche and adopt their phenotype. Abstract : What's new? Kupffer cells (KCs) reside within the liver, where they function in immunity and metabolism. The involvement of KCs in cancer, however, particularly in the pathogenesis of hepatocellular carcinoma (HCC), is unclear. In our study, the significance of KCs in HCC was investigated using a Clec4F‐diphtheria toxin receptor mouse model to temporally deplete KCs. Deletion of embryonic KCs led to replacement by monocyte‐derived KCs at HCC onset, with no impact on cancer development. Likewise, depletion of KCs at advanced‐stage HCC affected neither HCC progression nor neoplastic growth following hepatic resection. The findings indicate that KCs have no relationship with HCC pathogenesis.